On the Step Type of Continuous Propagating Positive Leader in Laboratory‐Scale Long Spark Discharges - Shengxin Huang; Weijiang Chen; Zhong Fu; Nianwen Xiang; Yujian Ding; Dengfeng Cheng; Jianwei Gu; Zhehao Pei (Geophysical Research Letters)
Abstract Positive leader steps are currently not well understood. Many recent findings challenge the previous understanding of the positive leader steps occurring in continuous leader development. In this work, we investigate the stepping propagation of positive leaders in laboratory spark discharge by using a high‐speed video camera and a synchronized electrical parameter measurement system. Two types of steps were distinguished in the positive leader continuous development process based on the current pulse features. One type of step exhibits a bell‐shaped current pulse, while the other type of step exhibits a steep current rise. The former type vanishes when the rising rate of the ambient electric field increases, whereas the latter type, which could be led by a separate luminous structure, does not.